The Basic Considerations of Judges Regarding the Testimony of Istifadah Witnesses in the Case of Itsbat Nikah (Study of the Determination of the Syar'iyah Court of Kualasimpang Number 10/Pdt.P/2021/MS.ksg): Dasar Pertimbangan Hakim Terhadap Kesaksian Saksi Istifadah Dalam Perkara Itsbat Nikah (Studi Penetapan Mahkamah Syar'iyah Kualasimpang Nomor 10/p.dt/p/2021/ms.ksg) - Mubarak, Husni; Rahmadani, Sindi (El-Hadhanah : Indonesian Journal Of Family Law And Islamic Law, 2022)
This research is based on a case which registered in Mahkamah Syar’iyah Kualasimpang as case number 10/Pdt.P/2021/MS.Ksg about istbat nikah wherein this case the witnesses who gave their testimonies were istifāḍah witnesses whereas an istifāḍah witness does not meet the criteria as a witness nor meet the matril requirements as regulated in clause 171 verse (1) HIR, clause 308 Rbg and 1907 The Book Of Civil Law all of which say every witness has to give their testimony based on what they saw, heard and experienced in an event while an istifāḍah witness had only heard rumor or story from someone else that an event has occurred. Based on this witnesses’ testimonies, judges authorized istifāḍah witnesses to give their testimonies to be heard in trial. Therefore researcher is interested to study further on howcome judges to consider the authorization of istifāḍah witnesses testimonies in istbat nikah case number 10/Pdt.P/2021/MS.Ksg and how Islamic law views the use of istifāḍah witnesses’ testimonies in an istbat nikah case. The methods used in this research are field study method and library study method with juridical normative approach. The result of the research claims that istifāḍah witnesses’s testimonies can be heard in trial as long as the testimonies given cannot be proved otherwise then the testimonies are true, it means as long the testimonies cannot be denied by another evidence, then two evidences in a form of document and testimony are sufficient, and by considering the matching of the testimonies given by the two witnesses then the testimonies given by istifāḍah witnesses are acceptable as judges’ preasumption, Islamic law views this matter can only be applied in some cases, one of which is istbat nikah case, with this in mind judges grant the pleader I and the pleader II their plead.